2010
DOI: 10.1186/1476-4598-9-193
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of mouse p53-deficient epidermal carcinoma defines molecular determinants of human cancer malignancy

Abstract: BackgroundThe epidermal specific ablation of Trp53 gene leads to the spontaneous development of aggressive tumors in mice through a process that is accelerated by the simultaneous ablation of Rb gene. Since alterations of p53-dependent pathway are common hallmarks of aggressive, poor prognostic human cancers, these mouse models can recapitulate the molecular features of some of these human malignancies.ResultsTo evaluate this possibility, gene expression microarray analysis was performed in mouse samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 51 publications
(81 reference statements)
4
33
0
Order By: Relevance
“…The majority of genes overexpressed in tumours are involved in cell cycle and, in particular, in mitosis26, in agreement with the described altered chromosome instability mediated by the epidermal loss of p5321. These genomic profiling studies also revealed a highly significant overlap with stem cell signatures and evidences of EMT processes, and demonstrated that these mouse tumours share relevant characteristics with multiple human malignancies distinguished by poor prognosis, altered p53 status and, remarkably, high metastasis incidence26. These data prompted us to analyze the possible metastatic capacities of spontaneous tumours arising in Rb ΔEC ; p53 ΔEC and p53 ΔEC mice.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The majority of genes overexpressed in tumours are involved in cell cycle and, in particular, in mitosis26, in agreement with the described altered chromosome instability mediated by the epidermal loss of p5321. These genomic profiling studies also revealed a highly significant overlap with stem cell signatures and evidences of EMT processes, and demonstrated that these mouse tumours share relevant characteristics with multiple human malignancies distinguished by poor prognosis, altered p53 status and, remarkably, high metastasis incidence26. These data prompted us to analyze the possible metastatic capacities of spontaneous tumours arising in Rb ΔEC ; p53 ΔEC and p53 ΔEC mice.…”
supporting
confidence: 83%
“…We have previously demonstrated that p53 ΔEC and Rb ΔEC ; p53 ΔEC derived tumours displayed a significant overlap with multiple human tumours characterized by augmented aggressiveness and metastatic development26. These included multiple epithelial cancers from different tissues of origin, such as breast and lung26. In particular, we observed that in non small cell lung cancer (NSCLC) a 20-gene signature derived from mouse p53-deficient tumours26, can stratify human patients and predict overall survival from a external dataset of human lung adenocarcinoma samples (Supp Fig 3A)57.…”
Section: Resultsmentioning
confidence: 99%
“…These associations agree with the present results: the p53 ΔEC and p53 ΔEC ;pRb ΔEC skin models both show ESC signatures as well as the deregulation of EMT markers [12]. Whether the transition from primary to invasive tumours in the Kras/Lkb1 L/L model is facilitated by early mutations inhibiting the p53-dependent pathway or in the p53 alleles themselves remains to be determined.…”
Section: Discussionsupporting
confidence: 92%
“…These similarities are particularly noticeable for human BC and LAd [12]. Further, the transcriptome of the mouse skin carcinomas shows strong similarities to that of embryonic stem cells (ESC), suggesting that p53 deficiency induces a potent de-differentiation process in epithelial cells [12]. p53-mutant human BCs show these ESC signatures too [14].…”
Section: Resultsmentioning
confidence: 95%
“…In consequence, this direct and miRNAdependent regulatory network is forming to regulate chemosensitivities and chemoresistances of this cancer. Meanwhile, p53, p63, and p73-related miRNA will provide a new potential target for molecular target therapies of p53-deficient tumors [105,106].…”
Section: New Prospects Of Mirna In Cancer Clinical Application Mirna mentioning
confidence: 99%